MOLECULAR STUDY OF GROWTH HORMONE AND GROWTH HORMONE RECEPTOR GENES IN MEHSANA BUFFALO - Mamta Janmeda; P.H. Vataliya (Indian Journal of Veterinary and Animal Sciences Research, 2024)
The study was conducted to find out polymorphism at various growth hormone (bGH) and growth hormone receptor loci (bGHR) by using PCRRFLP technique. Fifty two blood samples of Mehsana buffalo were collected from Livestock Research Station, Sardarkrushinagar Agricultural University, Gujarat. The DNA samples were subjected to PCR amplification using bGH and bGHR specific primers. The PCR products of GH1 (436 bp), GH2 (891bp), GH3 (441bp) and GHR1 (approx 640 bp) loci were digested with Alu 1, Msp 1, Hae III and Mae II restriction enzymes respectively and only AA, CC, FF and RR genotypes were respectively found in Mehsana buffalo. All the bGH and bGHR loci studied were monomorphic.